PENGARUH BOOK TAX DIFFERENCES, ARUS KAS OPERASI, TINGKAT HUTANG DAN UKURAN PERUSAHAAN TERHADAP PERSISTENSI LABA (Pada perusahaan sub sektor basic dan chemical yang terdaftar di Bursa Efek Indonesia periode 2014-2018) - Imam Hidayat; Syifa Fauziyah (COMPETITIVE, 2020)
This study aims to determine the effect of book tax differences, operating cash flow, debt levels and company size on earnings persistence in basic and chemical sub-sector companies listed on the Indonesia Stock Exchange (IDX). The time period of the study is 5 years, namely the 2014-2018 period.This research population includes all basic and chemical sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The sampling technique uses purposive sampling technique. Based on predetermined criteria obtained by 10 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis.The results showed that book tax differences had no effect on earnings persistence, operating cash flow had a positive effect on earnings persistence, the level of debt had no effect on earnings persistence and company size had no effect on earnings persistence.